HUMAN CAPITAL MANAGEMENT DAN TECHNOLOGY ACCEPTANCE MODEL SERTA PENGARUHNYA TERHADAP PRODUKTIVITASKERJA KARYAWAN PADA PERUSAHAAN SEKTOR PERKEBUNAN - Mazka, Furqon (PUBLISHER ABISATYA DINAMIKA ISWARA PUBLISHING, 2023)
Companies need a directed and sustainable strategy in managing and developing human resources so that the expected productivity is achieved. Productivity is a measure of the success of a company and/or industry. This study aims to see whether human capital management and technology acceptance models can affect employee productivity. The research method used is descriptive quantitative which aims to describe situations and events, as well as explain the influence of research variables, while the number of samples used in this study were 220 people. The results of the study show that the Human Capital Management carried out by PTABC VI and PTABC VIII is optimal enough to affect Productivity, as well as that the Technology acceptance model carried out by PTABC VI and PTABC VIII is optimal enough to affect Productivity